2012
DOI: 10.1002/cne.23070
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic evidence for spatially clustered spines in apical dendrites of monkey neocortical pyramidal cells

Abstract: The general organization of neocortical connectivity in rhesus monkey is relatively well understood. However, mounting evidence points to an organizing principle that involves clustered synapses at the level of individual dendrites. Several synaptic plasticity studies have reported cooperative interaction between neighboring synapses on a given dendritic branch, which may potentially induce synapse clusters. Additionally, theoretical models have predicted that such cooperativity is advantageous, in that it gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 77 publications
(105 reference statements)
2
55
0
Order By: Relevance
“…Dendrites regulate the integration of inputs and provide sites for synapses on spines (41, 42). As such, they are extremely plastic structures that undergo changes in response to experience, which is especially evident during development (12,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). For this reason, a delay in the formation of dendritic trees in the prefrontal cortex may be important for processing and integrating the extensive load of information that both humans and chimpanzees acquire during development and for maintaining plasticity of executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites regulate the integration of inputs and provide sites for synapses on spines (41, 42). As such, they are extremely plastic structures that undergo changes in response to experience, which is especially evident during development (12,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). For this reason, a delay in the formation of dendritic trees in the prefrontal cortex may be important for processing and integrating the extensive load of information that both humans and chimpanzees acquire during development and for maintaining plasticity of executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical clustering has also been documented in the primate cortex (Yadav et al, 2012). Analysis of the locations of spines in the prefrontal cortex of rhesus monkeys confirmed the preference for spatial spine clustering.…”
Section: Dendritic Branches As Key Computational Elementsmentioning
confidence: 97%
“…As detailed in section 2.4., an increasing number of studies have shown that synaptic contacts can group together within a short stretch of the dendritic branch, forming anatomical clusters 2 (Makino & Malinow, 2011; Yadav et al, 2012) and/or create functional clusters whereby several neighboring synapses are activated synchronously (Fu, Yu, Lu, & Zuo, 2012; Kleindienst, Winnubst, Roth-Alpermann, Bonhoeffer, & Lohmann, 2011; Takahashi et al, 2012), in the absence of obvious spine density changes This patterned spatial synaptic arrangement along with concrete evidence of dendritic spike generation both in vitro (Ariav et al, 2003; Häusser et al, 2000; S. Kim et al, 2012; Larkum & Nevian, 2008; Losonczy & Magee, 2006; Makara & Magee, 2013; Nevian et al, 2007; Schiller et al, 2000a) and in vivo (Lavzin et al, 2012; Major et al, 2013; S.…”
Section: Dendritic Branches As Key Computational Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Yadav et al [33] found that anatomical spine clusters (groups of three or more) occur significantly more frequently than chance within apical dendrites of layer III cells of the monkey prefrontal cortex. This study reveals the capability of neurons to spatially organize spines, but it does not prove a causal relationship between functional and structural changes.…”
Section: Synapse Clusteringmentioning
confidence: 99%